Usability Testing on the Simponik Website using the System Usability Scale (SUS) - Saputra, Deni; Ardiyan Syah, Edo; Darnis, Febriyanti (Politeknik Ganesha Medan, 2022)
SIMPONIK is one of the websites developed by the Furniture and Wood Processing Industry Polytechnic to answer the challenges during online learning due to covid 19 and the large number of guests visiting because it is located in an Industrial Estate. To improve the website's service and user experience, there must be testing of the website's usability. The purpose of this study is to test the usability of the SIMPONIK website as a basis for improving the appearance and services available on the website. This study uses the System Usability Scale (SUS) method by distributing questionnaires to 100 respondents. From the results of this study, the SUS score was 76,025, which means the SUS category is acceptable (71-100). Although the results are categorized as acceptable, there must be improvements must be made, especially in terms of practicality and convenience for users.